2022
DOI: 10.48550/arxiv.2206.10515
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Root-$T \overline{T}$ Deformations

Abstract: In this letter we introduce a one-parameter deformation of two-dimensional quantum field theories generated by a non-analytic operator which we call Root-T T . For a conformal field theory, the operator coincides with the square-root of the T T operator. More generally, the operator is defined so that classically it is marginal and generates a flow which commutes with the T T -flow. Intriguingly, the Root-T T flow is closely related to the ModMax theory recently constructed by Bandos, Lechner, Sorokin and Town… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Note Added: After we completed the project, Ref. [26] appeared on arXiv, which has some overlap with our results on scalar ModMax theory as a root flow equation.…”
Section: Scalars Modmax Theory From Marginal T T -Deformationmentioning
confidence: 86%
“…Note Added: After we completed the project, Ref. [26] appeared on arXiv, which has some overlap with our results on scalar ModMax theory as a root flow equation.…”
Section: Scalars Modmax Theory From Marginal T T -Deformationmentioning
confidence: 86%
“…Note added. On June 22 nd 2022, the day the second version of this work was made public on arXiv, the manuscript [34] appeared. In [34], it is independently shown that the…”
Section: Acknowledgmentsmentioning
confidence: 99%